Treatment patterns and healthcare costs among patients with psoriasis initiating apremilast or biologics: a retrospective claims database cohort analysis - Jashin J. Wu; Ching An Wang; Greeta Jobson; David Davidson; Samaneh Kalirai; Julia Zhu; Manasi Suryavanshi; Mayank Mittal; Vardhaman Patel; Lauren Seigel (Taylor & Francis Group, 2023)
Objective This study aimed to compare treatment patterns and healthcare costs for patients with psoriasis who initiate apremilast, tumor necrosis factor inhibitor, or interleukin inhibitor. Methods This retrospective cohort study used Optum Clinformatics® Data Mart to identify propensity score-matched patients initiating apremilast, tumor necrosis factor inhibitors, or interleukin inhibitors, with 12-month baseline and 24-month follow-up data. Switch, discontinuation, persistence, healthcare resource utilization, and total healthcare costs were assessed. Results Twenty-four-month switch rates were highest for tumor necrosis factor inhibitors (32%), followed by apremilast (21%) then interleukin inhibitors (14%). Mean (SD) per-patient-per-month costs for switchers were lowest for apremilast ($4213 [$2304]), higher for tumor necrosis factor inhibitors ($5274 [$2280]), and highest for interleukin inhibitors ($5539 [$2296]; p < .001), primarily attributable to pharmacy costs: $3466 (apremilast), $4432 (tumor necrosis factor inhibitor), and $4721 (interleukin inhibitor). Limitations Psoriasis severity is absent from claims data; cost outcomes may be influenced by more severe psoriasis being more costly. Conclusion Switching psoriasis treatment is common and increases over time. Apremilast initiators had lower switch rates and costs compared with tumor necrosis factor inhibitors, despite lower effectiveness reported in previous studies, perhaps indicating patient preference for oral treatment. Additional oral options may be desirable for this population.